Implementasi Pendidikan Kewirausahaan (Entrepreneurship) di Sekolah Dasar/Madrasah Ibtidaiyah - Muhamad Afandi (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study aims to discuss and see the evaluation of entrepreneurship education in elementary schools / madrasah ibtidaiyah. Elementary schools and madrasah ibtidaiyah that have implemented entrepreneurship education that can be used as references include: SD Entrepreneur Muslim Alif-A Piyungan Yogyakarta, SD IT Alam Harum Purbalingga, and MI Terpadu Qurrota A'yun Ponorogo. This research uses a qualitative approach. This type of research data is qualitative data and the data source is secondary data. While the data method used is library research (library research). Data analysis techniques through data reduction, data display, and withdrawal from the literature study conducted. Meanwhile, to check the validity of the data using triangulation of data sources. The results of this study explain that, the implementation of Entrepreneurship Education in elementary schools / madrasah ibtidaiyah can be carried out in three stages, namely: (1) The planning stage, including: formulation of program objectives, program vision and mission of entrepreneurship education, material which then incorporates educational values. entrepreneurship that will be developed in the Learning Implementation Plan; (2) Implementation stage, including: class, entrepreneurship, integrated with subjects, self-development activities, school culture; and (3) The evaluation phase, including entrepreneurial education activities based on entrepreneurial values that have been internalized and implemented in the behavior seen in the activities of students at school.